Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo - Kakizoe, Showtaro; Maruyama, Munetoshi; Masumoto, Kimio (Zootaxa, 2019)
Megasybacodes brevitarsis Kakizoe, Maruyama & Masumoto, a new genus and new species of the tribe Rhyparini, is described based on a single female from Borneo. It is allied to the genus Sybacodes Fairmaire, 1896, but easily distinguished by its short protarsi, broad flattened basal tarsomeres of the meso- and metatarsi, broad flattened tibiae, and wrinkled pronotal and elytral surfaces. Checklist of rhyparine species from Borneo is also provided.